Autonomous racing on unseen tracks using reinforcement learning - Jefferies, Devin Wayne Patrick (Stellenbosch : Stellenbosch University, 2025)
Jefferies, D. W. P. 2025. Autonomous racing on unseen tracks using reinforcement learning. Unpublished masters thesis. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/43e6d233-2024-46d0-9ae8-ba3029360954